Push count: a novel and quantitative approach to assessing second-stage labor progress in obese and non-obese patients - Tina M. Bui; Kayla M. Witcik; Kristina A. Roloff; Michael G. Ross; Guillermo J. Valenzuela (The Journal of Maternal-Fetal & Neonatal Medicine)
Objective Current definitions of second-stage labor arrest rely on arbitrary time limits—at least 2 h for multiparous patients and 3 h for nulliparous patients—yet the utility of these time-based definitions remains limited due to their failure to account for physiologic variability and rest periods. This study evaluates alternative metrics, including total pushes, pushing duration, and pushing force, to better quantify second-stage labor progression. We hypothesized that patients with obesity would require more pushes and spend more time pushing, with an anticipated increase in cumulative force.Methods We conducted a prospective observational study of nulliparous term patients with singleton pregnancies at a single tertiary care center. Patients were grouped by BMI at admission (< 35 kg/m2 vs. ≥ 35 kg/m2) to evaluate differences in pushing effort and delivery outcomes. The primary outcomes—total number of pushes, cumulative pushing time, and expulsive force—were assessed among patients who achieved a vaginal delivery. Secondary outcomes included labor characteristics, maternal morbidity, and neonatal outcomes. Statistical comparisons between BMI groups were performed using appropriate parametric or non-parametric tests.Results Among 273 patients, the mean second-stage duration was 82.5 min, involving 54.9 pushes and 11.2 min of active pushing. Patients who exceeded the 90th percentile for push count (116 overall; 104 for BMI < 35 kg/m2 and 141 for BMI ≥ 35 kg/m2) were significantly more likely to undergo cesarean delivery. Patients with obesity (BMI ≥ 35 kg/m2) required, on average, 18 more pushes (p = 0.001) and 2 additional minutes of pushing efforts (p = 0.011) to achieve vaginal delivery. This association remained true after excluding operative and cesarean deliveries. Operative and second-stage cesarean deliveries involved significantly more total pushes compared to spontaneous vaginal deliveries (58 vs. 40.5, p = 0.012), and the rate of operative delivery increased sixfold once the number of pushes exceeded 115.Conclusion Patients with obesity demonstrated a need for increased effort to achieve vaginal delivery, including a higher number of pushes and a longer pushing duration. These findings support using the 90th percentile threshold for total pushes (116 overall; 104 for BMI < 35 kg/m2 and 141 for BMI ≥ 35 kg/m2) as a clinically meaningful benchmark for assessing second-stage labor progression, given the observed rise in operative and cesarean delivery rates beyond this point. Incorporating these objective metrics into labor management may allow for a more individualized and physiologically grounded approach to evaluating second-stage progress.